Seismic Performance of Elevated Reinforced Concrete Water Tanks - Tripathi, Sandesh Sagar; Thapa, Kamal Bahadur (Journal of the Institute of Engineering, 2021)
Most of the codal provisions used worldwide for the design of elevated water tanks incorporates the nonlinear response through reduction factor that considers overstrength, ductility and redundancy. The majority of these codes provide a value which incorporates the demand of their geological condition and construction industry. In Nepal, there is lack of own guidelines and codes for the seismic design of elevated water tanks. In the present work, seismic performance of elevated reinforced concrete (RC) Intze type water tank is evaluated and value of the response reduction factor (R) for the design of such tank is determined. In this research work 34 models of elevated reinforced water tank were analyzed using SAP 2000 to evaluate the seismic performance with varying tank filling condition and staging height for 450 cumec and 225 cumec capacity. Based on the results, it is concluded that single value of response reduction factor cannot be justified for all heights and capacity of elevated RC water tank. So, for economical design purpose, estimation of response reduction factor with exact analysis is preferred.